Outsourcing Strategy in Avionics Manufacturing in Indian DPSUs - Lakshman Singh; Alpana Srivastava (International Journal of Supply Chain Management, 2018)
The Avionics manufacturer DPSUs is a high end technology oriented which involve in complex integration among their supplier vendors. The global competition of DPSUs not only related the manufacturing facility technology but also their supply chain. This research paper point out the outsourcing as a strategic tool for economic growth of DPSUs. In this paper researcher discuss the present challenges in supply chain for avionics manufacturer DPSUs and GOI policy for outsourcing. Researcher develop a strategic outsourcing model for avionics manufacturer DPSUs which application enhances their performance.